Helicobacter pylori Infection in Ontario: Prevalence and Risk Factors - Farah Naja; Nancy Kreiger; Terrence Sullivan (Canadian Journal of Gastroenterology)
BACKGROUND: Helicobacter pylori has been classified by the World Health Organization as a type I carcinogen. Nearly 50% of the world’s population is estimated to be infected with H pylori. Prevalence patterns of the infection are different between developing and developed countries. The present study had two objectives – to estimate the prevalence of H pylori infection in Ontario, and to evaluate the relationship between the infection and various demographic characteristics and selected lifestyle factors.